Formaldehyde-doxorubicin dual polymeric drug delivery system for higher efficacy and limited cardiotoxicity of anthracyclines. (15th January 2021) - Ordonez, Estela; Kendrick-Williams, Laken L.; Harth, Eva
Graphical abstract: Highlights: Dual drug delivery system providing 4-fold higher efficacy of DOX. Formaldehyde and Dox form DNA adduct to increase efficacy but also decrease cardiotoxicity through this mechanism. Formaldehyde first use in a polymeric prodrug. Cardiotoxicity is reduced through the formation of the DNA-DOX adduct as indicative in the high efficacy. Abstract: We report the synthesis of a dual delivery system composed of chemically bound pH-responsive formaldehyde polymer prodrugs and pH-responsive doxorubicin loaded nanoparticles to increase the therapeutic index of doxorubicin by working in synergy with formaldehyde to enable the formation of DOX-DNA adducts and limiting the cardiotoxicity of anthracyclines. Polyacrylates bearing 1, 2- and 1, 3- pendant diols were synthesized via reversible addition fragmentation chain transfer (RAFT) polymerization to conjugate formaldehyde, forming 5- or 6-membered acetal rings with tunable conjugation percentages (1.5–10 wt%) for controlled release in acidic environments of the tumor extracellular matrix. The formaldehyde-conjugated prodrugs are then combined with polyester nanoparticles formed by intermolecular crosslinking via oxime click chemistry of less than 200 nm in size containing 14 wt% encapsulated Doxorubicin (DOX). Release kinetics show a sustained release of both DOX and formaldehyde at pH 5.0, mimicking the low pH of the tumor environment whereas insignificant release was recorded at physiological pH. The cell viability of the dual delivery system combination was evaluated in 4 T1 breast cancer cells resulting in a considerably increase of cell death of about 4-fold compared to free DOX alone. The protective effect of formaldehyde towards DOX- induced damages was observed in Lactate dehydrogenase assays with cardiomyocytes (P1-3). The resulting polymeric delivery system is the first reported example of a DOX and formaldehyde co-administration, demonstrating the potential significant effect of formaldehyde towards an improved anti-cancer efficacy and reduced cardiotoxicity of DOX.